Democratização ou Elitização? Um estudo sobre o perfil dos estudantes ingressantes do Ensino Médio Integrado ao Técnico do Instituto Federal do Norte de Minas Gerais (IFNMG) Campus Januária - Sonia Sousa Almeida Rodrigues (2018)
The federal network of professional and technological education registers, in recent brazilian history, a scenario of expansion and reordering by the Organization of the Federal Institutes of Education, Science and Technology (IFs), proposed by the Ministry of Education and Culture (MEC) in 2007 (Decree Nº 6,095/2007). The IFs were organized with the purpose to offer vocational and technology education at all levels and modalities, especially the average level. Within the meaning of the MEC, different from the trends that guided the professional education with a focus on technical preparation for the market, the Organization of these Institutes is heading for the training of professionals for the world of work and is based on a project of social inclusion of historically excluded sectors in the country. The present study intended to analyze the profile of students entering the high school Integrated Federal Institute of North of Minas Gerais (IFNMG) Januária Campus in order to contribute to the debate about social inclusion project set to the IFs. To achieve the objective proposed methodology chosen, for exploratory research and descriptive and a case study. The study included qualitative and quantitative analysis of the data. Collection procedures used electronic questionnaires, which were applied for 188 students, and documentary analysis. The results obtained allowed to show that the profile of students entering high school integrated IFNMG Campus Januária is characterized by those looking for a free, public education, and that mostly come from low income family.